"Eco-Conscious Concrete Manufacturing: Exploring the Potential of Waste Marble Powder "" (International Journal of Food and Nutritional Sciences, 2022)
The advancement of concrete technology is reducing the consumption of natural and energy resources, and reduces the environmental pollution by the industrial waste. Marble is industrially processed by being cut, polished and used for decorative purposes. Marbles are generated in stone processing plant which pollute the environment and affect the humans directly or indirectly. Marble is industrially processed by being cut, polished and used for decorative purpose and thus, economically variable. During cutting process, 20%-30% of a marble block becomes waste marble powder. Since, it leads to a serious environmental problem, therefore, use of waste marble powder in the concrete production as a partial replacement of cement or to be added as an admixture. Reckon fibre was also added to increase compressive strength of concrete. This concrete is more environments friendly and will give more life to concrete. Pozzalanic concrete using marble dust powder show that this concrete gives better compressive strength and increases durability of concrete.